PSIKOLOGI DALAM TRADISI ILMIAH ISLAM - Norhidayat, Norhidayat (Fakultas Ushuluddin dan Humaniora IAIN Antasari, 2013)
This paper described about psychology which had been discussing in the traditions ofÂ Islamic thought. Either in religious perpective, Sufiâs or philosophyâs, the psychology inÂ the traditions of Islamic thought was basically different from the psychology in theÂ tradition of western-secular thought. However the last psychology was reduced as aÂ study of mind and behavior or mental processes, the other has been a study of soul asÂ immaterial substansions, it was neither of body nor part of body, it would be existÂ whenever the body had been died and each may be repaid what it had earned.